The Effectiveness of Information Verification Services through the Klinik Hoaks Website at the Department of Communication and Informatics of East Java Province - Karisma, Herdyana Lady; Pradana, Galih Wahyu; Ma’ruf, Muhammad Farid; Eprilianto, Deby Febriyan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The rapid development of information and communication technology has driven significant changes in the implementation of public services, particularly in the dissemination of information to the public. The increasing accessibility of the internet enables information to spread quickly, but also raises the potential for the circulation of false or misleading information. This condition requires the government to provide public information services that are accurate, responsive, and easily accessible in order to protect society from the negative impacts of misinformation. The Government of East Java Province, through the Department of Communication and Informatics, provides a digital-based information verification service through the Klinik Hoaks Website to assist the public in clarifying questionable information. This study aims to assess the effectiveness of the service based on Duncan’s organizational effectiveness theory, which includes goal attainment, integration, and adaptation. This research employs a qualitative approach with a descriptive design. Data collection techniques include observation, interviews, and documentation, with informants selected using purposive sampling. The results show that the Klinik Hoaks Website service has generally been effective. The service is able to meet the public’s need for information verification, has procedures that are easy to understand, and is supported by adequate facilities. However, several challenges remain, including inconsistency in verification time, limited outreach of socialization, and the absence of specific technical regulations. Therefore, improvements are needed in terms of service timeliness, broader dissemination, and strengthening of technical regulations to optimize the effectiveness of the service.